Terapi Solat Dalam Menangani Penyakit Gelisah (Anxiety) Menurut Perspektif Psikoterapi Islam - Azizan, Ahmad Hisham; Sa'ari, Che Zarrina (Jurnal Usuluddin, 2009)
Prayer is a form of worship that is very important in the framework of the construction of human relationship with the Creator. The practice of prayer thereof not only refers to the implementation of the law (Shari`ah) alone, but it also has a significant effect on the purification of human life and physical health. One positive effect of prayer is in dealing with anxiety suffered by people. This article discusses the position of prayer and its relevance in dealing with anxiety and mental and physical health of people.